2023
DOI: 10.3390/rs15112703
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Transitions and the Associated Impacts on Carbon Storage in the Poyang Lake Basin, China

Abstract: Carbon storage plays an important role in the global carbon cycle and climate change mitigation. Understanding the relationship between land use change and carbon storage can significantly contribute to carbon neutrality and sustainable development. However, most previous studies only analyze the carbon storage change due to land use change, while few studies quantitatively evaluate the contributions of various land use transitions (LUTs) to carbon storage change, which cannot provide enough information for la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Fortunately, the geo-informatic Tupu model provides a spatio-temporal analysis technique that is capable of delineating the spatial structural traits and temporal shifts of events through advanced data mining and specific processing techniques. This method, by creating a series of intuitive graphs, images, and schematic information in the form of Tupu units, aids in the visualization of the processes of LUCs [59][60][61][62][63]. Essentially, the geo-informatic Tupu model allows for the recording of complex spatiotemporal land-use data using Tupu units, which enhances the precision, clarity, and realism of LUCs research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fortunately, the geo-informatic Tupu model provides a spatio-temporal analysis technique that is capable of delineating the spatial structural traits and temporal shifts of events through advanced data mining and specific processing techniques. This method, by creating a series of intuitive graphs, images, and schematic information in the form of Tupu units, aids in the visualization of the processes of LUCs [59][60][61][62][63]. Essentially, the geo-informatic Tupu model allows for the recording of complex spatiotemporal land-use data using Tupu units, which enhances the precision, clarity, and realism of LUCs research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, it is extensively utilized in various applications [15][16][17][18]. Research has shown that the InVEST model, combined with geographic information mapping, was used to simulate carbon storage in the Poyang Lake basin [19]. In addition, some scholars have also used land use types in conjunction with the InVEST model to quantitatively assess the impact of LUCC conversion on ecosystem carbon storage [20].…”
Section: Introductionmentioning
confidence: 99%
“…Land, as the primary arena for human activities, has undergone drastic changes owing to accelerating socioeconomic development, urbanization processes, and natural transformations by human beings 1 , 2 . Land-use change forms the foundation of the study of carbon storage in terrestrial ecosystems, as it directly impacts the original pattern, process, function, and structure of terrestrial ecosystems, thereby altering their carbon storage 3 , 4 . This directly affects climate change predictions, greenhouse gas emissions, and reduction efforts 4 .…”
Section: Introductionmentioning
confidence: 99%